Excess weight: a nutritional risk among basic education teachers (Research, Society and Development, 2023)
Objective: To determine the nutritional profile of teachers in Rio Paranaíba, MG. Methods: Blood pressure was assessed; anthropometric measurements (weight, height, waist and neck perimeters, and biceps, triceps, subscapular and suprailiac skinfolds); sociodemographic characteristics and lifestyle habits. For data analysis, Student's t-test, Chi-square test or Fisher's exact test were used, both at 5% significance. Results: Among the 103 evaluated, most were female, 61.17% had a nutritional diagnosis of overweight, and 69.90% had increased body fat. An increase in blood pressure levels were observed in 15.53% of those evaluated, 33.01% in the waist perimeter and 36.89% in the neck perimeter. There was a statistical difference between the classification of the nutritional status of overweight with the presence of diseases, and the daily intake of processed, fatty and/or sugary foods. There was no association between the classification of nutritional status and the practice of physical activity and consumption of fruits and vegetables. Conclusion: Most of the individuals evaluated showed compromised nutritional status, making it necessary to adopt short and long-term measures to reverse nutritional deviations in this population.